Impact of the PROCESS guideline on the reporting of surgical case series: A before and after study. (September 2017) - Agha, R.A.; Borrelli, M.R.; Farwana, R.; Kusu-Orkar, T.; Millip, M.C.; Thavayogan, R.; Garner, J.; Darhouse, N.; Orgill, D.P.
Abstract: Introduction: The PROCESS guideline was developed in 2016 through expert Delphi consensus. It aimed to improve the quality of reporting of surgical case series. This study assessed the impact of the introduction of the PROCESS guideline on reporting for surgical case series submitted to three journals. Methods: 20 case series published in the International Journal of Surgery Case Reports (IJSCR), the International Journal of Surgery (IJS) or the Annals of Medicine and Surgery (AMS) in September to December 2016, prior to the introduction of the PROCESS guideline (the pre-PROCESS period), were randomly identified and scored against the PROCESS criteria. Two authors independently scored each article a total score out of 29, the 'PROCESS score' (expressed as a percentage). Scores for the two researchers were compared and consensus was reached to achieve a final score set. The process was repeated for the January 2017 to April 2017 issues of the three journals, post PROCESS implementation (the post-PROCESS period). Results: The mean PROCESS score was 80% (range 66–90%) for the pre-PROCESS period and 84% (range 72–95%) for the post-PROCESS period, a 4% relative increase [STATS]. The Cohen's Kappa score between researchers was 0.907 implying very substantial agreement. Conclusion: Implementation of the PROCESS guideline resulted in a 5% improvement in the reporting quality of surgical case series published in three journals. Further research is needed to identify and successfully navigate existing barriers to greater compliance. Authors, reviewers and editors should adhere to the guidelines to boost reporting quality. Journals should develop their policies and guide for authors to incorporate the guideline and mandate compliance. Highlights: This is the first assessment of the PROCESS guidelines since its publication. There was a 5% increase in concordance with the PROCESS guidelines after publication. Research is needed to identify and navigate existing barriers to greater compliance. Authors, reviewers and editors should adhere to the guidelines to boost reporting quality.